The Combined Effect Of Extract Of Tamarindus Indica L. Leaves And Annona Muricata L. Leaves On Blood Glucose Levels In Male Rats Wistar Strain Induced Alloxan - Eka Wisnu Kusuma; Eka Safarini; Devina Ingrid Anggraini (Universitas Muhammadiyah Magelang, 2019)
A recent study States that the leaves of the tamarind and soursop can lower blood glucose levels with a single dose. This research was conducted to find out the influence of the combination of ethanol extracts of leaves of the tamarind and soursop leaf in mice induced aloksan. Test treatment consists of 8 groups, normal, negative control (aloksan), positive (glibenklamid), the dose I (tamarind), dose II (soursop), AJ III dosage: SIR 25:75 dose), IV (AJ: SIR 50:50), dosage V (AJ: SIR 75:25). All groups (except normal) induced with aloksan 160 mg/KgBB. Then proceed with a test of treatment of each group of the drug start day 0 up to 14 in per-oral. The taking of blood glucose levels is done on the day 0, 7 and 14. Administering ethanol extracts of leaves of tamarind and soursop both single and combination capable of lowering blood glucose levels seen from the average hypoglycemic